2010
DOI: 10.5380/raega.v20i0.20619
|View full text |Cite
|
Sign up to set email alerts
|

Uso De Espécies Da Caatinga Na Alimentação De Rebanhos No Município De São João Do Cariri – Pb

Abstract: Objetivou-se efetuar o levantamento das espécies vegetais da caatinga utilizadas na alimentação dos rebanhos, tipo de suporte alimentar oferecido aos animais na época seca, ocorrência de armazenamento da alimentação e redução dos rebanhos na época seca. Foram aplicados questionários a população rural de São João do Cariri - PB e confeccionado o mapa das propriedades rurais. Foi constatado que a maioria das propriedades apresenta baixos índices zootécnicos, com rebanhos pequenos, distribuídos entre bovinos, ovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
6
Order By: Relevance
“…Furthermore, as many Caatinga plant species exhibit protective mechanisms (spines and thorns, unpleasant taste, toxic compounds, hirsute leaves; Pfister & Malechek, ; Figueiredo, Araújo, Pereira, Bakke, & Bakke, ; Araújo‐Filho, ; Sebata, ; Oliveira et al., ), palatable and unprotected species may decline in abundance due to selective grazing (Wan et al., ; Oliveira et al., ). In addition, goats are known to browse on twigs, leaves, or on the bark of trees and cacti (Araujo, Dantas, de Andrade, Parente, & Érllens, ). However, in our study area, trees and cacti with damaged trunks were only observed occasionally (own observation), and thus the overall direct impact of browsing on these plant types is expected to be low.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as many Caatinga plant species exhibit protective mechanisms (spines and thorns, unpleasant taste, toxic compounds, hirsute leaves; Pfister & Malechek, ; Figueiredo, Araújo, Pereira, Bakke, & Bakke, ; Araújo‐Filho, ; Sebata, ; Oliveira et al., ), palatable and unprotected species may decline in abundance due to selective grazing (Wan et al., ; Oliveira et al., ). In addition, goats are known to browse on twigs, leaves, or on the bark of trees and cacti (Araujo, Dantas, de Andrade, Parente, & Érllens, ). However, in our study area, trees and cacti with damaged trunks were only observed occasionally (own observation), and thus the overall direct impact of browsing on these plant types is expected to be low.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mandacaru for food included both nonhuman animals (see, for example, Cavalcanti & Resende 2006) Mandacaru is one of the main forage resources for ruminant animals during the prolonged drought periods in Northeast Brazil. Because of this, many agriculturalists of this region cultivate mandacaru to support their herd Animal food (forage) Cavalcanti & Resende 2006;Santos et al 2007;Araújo et al 2010;Damasceno et al 2010;Silva et al 2011;Lucena et al 2012b;2015;Pereira Filho et al 2013;Roque & Loiola 2013;Silva et al 2013;Alves et al 2014;Sales et al 2014;Pereira Júnior et al 2015;Santana Neto et al 2015 Cereus jamacaru DC. (Cactaceae): From 17 th century naturalists to modern day scientific and technological prospecting and to sell to other ranchers (Sales et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…One hundred percent of the evaluated plants nodulated, regardless of the soil in which they were grown. According to Araujo et al (2010), M. tenuiflora is a widely occurring Fabaceae plant in the north-eastern Brazilian states found in the Caatinga vegetation and presents low symbiotic specificity. The species with the second highest nodulation index was M. atropurpureum, which reached 100% nodulation in soils from the Sertânia and Arcoverde locations, with a small decrease when cultivated in the soil from the sampling areas of the municipality of São Bento do Una (92.5%).…”
Section: Resultsmentioning
confidence: 99%